Root cause of reinforced concrete dapped-end beams failure - Aswin, M. (Research India Publications, 2015)
The failure mode of 111 RC dapped-end beams are presented and evaluated. The 93.69 of the tested beams were failed in shear at the re-entrant corners of the dapped-end region. Although many strengthening methods have been used to strengthening the dapped-end region, only the load-deflection relationship of the beams were improved. However, test results of 4 large scale RC dapped-end beams showed that the highest stress concentration factors were recorded at the re-entrant corners compared to other area of the dapped-end region of the beam. Â© Research India Publications.